Features of the legal regulation of investment activities in relation to natural resources in the EAEU countries - Shakhray, Irina S. (Journal of the Belarusian State University. Law, 2019)
The article analyzes the specifics of the legal regulation of investment activities in relation to natural resources in the Republic of Belarus and other countries-members of Eurasian Economic Union. The approaches of the named countries are being studied to secure ways of making investments in the natural resource sphere, providing investors with access to land and other natural resources. The system and development prospects of investment forms of nature management are investigated, in particular, concessions, as well as it is proposed to develop the investment potential of the lease in the field of natural resources. On this basis, some recommendations were made to improve Belarusian legislation.
Keywords: investment activities; natural resources; nature management; natural resources legislation; investment legislation; concession; EAEU